The Effect of Cooperative Learning Method Enhanced with Metacognitive Strategies on Students' Metacognitive Skills in Math Course - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2017)
The purpose of this research was to investigate the effect of cooperative learning method enhanced with metacognitive strategies on metacognitive skills of 6th grade students in mathematics education. The research was designed as a mixed method in which qualitative and quantitative methods were used together. The quantitative research was planned as a pre-test post-test control group quasiexperimental design. Document review method, one of the qualitative research techniques, was used to obtain qualitative data. The research participants were composed of 101 6th grade students. Cooperative learning method enhanced by metacognitive strategies was used in the first experimental group and only cooperative learning method with no support of metacognitive strategies was used in the second experimental group. There was no intervention for the control group. Data were collected using the Junior Metacognitive Awareness Inventory (Jr. MAI) developed by Sperling, Howard, Miller, and Murphy (2002) and through the written opinions of the students about implementation process. The quantitative data was analyzed by performing the dependent group t-test and analysis of variance. For the qualitative section, data was analyzed using descriptive analysis. According to the results of the data analysis, at the end of the interventions, it was seen that the levels of metacognitive skills of the first experimental group were significantly higher than of both the second experimantal group and the control group. Also, the levels of metacognitive skills of the second experimental group were higher than those of the control group. According to the results based on the analysis of students' views, it was seen that, the students in the first experimental group expressed their thoughts on the development of their metacognitive skills. In this context, it was observed that, the students' questioning the problems and their solution processes, analyzing their mistakes and their planning skills have been improved. Also, the second experimental group students stated that they did reciprocal questioning on paired worksheets and their group work skills improved.
Keywords: Cooperative learning method; Metacognition; Metacognitive strategies; Mathematics education; Student team achievement division; META-COGNITIVE INSTRUCTION; MATHEMATICS; SELF; KNOWLEDGE; SCIENCE; ABILITY; 3RD